2021
DOI: 10.4236/ojmsi.2021.92009
|View full text |Cite
|
Sign up to set email alerts
|

Worker’s Helmet Recognition and Identity Recognition Based on Deep Learning

Abstract: For decades, safety has been a concern for the construction industry. Helmet detection caught the attention of machine learning, but the problem of identity recognition has been ignored in previous studies, which brings trouble to the subsequent safety education of workers. Although, many scholars have devoted themselves to the study of person re-identification which neglected safety detection. The study of this paper mainly proposes a method based on deep learning, which is different from the previous study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Nath et al [23] proposed a real-time You-Only-Look-Once (YOLO) architecture for the verification of PPE compliance of workers, i.e., whether or not a worker was wearing a hard hat, vest, or both. Moreover, human identity recognition and helmet detection was performed using YOLOv3 architecture in [24]. Wang et al [25] compared the performance of various architectures of the YOLO family (YOLOv3 [16], YOLOv4 [26], and YOLOv5 [27]) on a custom dataset, named as the CHV dataset, and found that YOLOv5x had a superior performance as compared to other models.…”
Section: Introductionmentioning
confidence: 99%
“…Nath et al [23] proposed a real-time You-Only-Look-Once (YOLO) architecture for the verification of PPE compliance of workers, i.e., whether or not a worker was wearing a hard hat, vest, or both. Moreover, human identity recognition and helmet detection was performed using YOLOv3 architecture in [24]. Wang et al [25] compared the performance of various architectures of the YOLO family (YOLOv3 [16], YOLOv4 [26], and YOLOv5 [27]) on a custom dataset, named as the CHV dataset, and found that YOLOv5x had a superior performance as compared to other models.…”
Section: Introductionmentioning
confidence: 99%
“…DIOU-NMS was employed to replace the traditional NMS, which improved the detection ability of the model for occluded workers and small targets. In [1,19], YOLOv3 and YOLOv4 algorithms were adopted to detect helmet wearing and worker falls, respectively. In addition to personnel detection, the YOLO detector was combined with UAV to perform real-time detection of the designated area [20,21], overcoming the problem of target omission and incorrect detection caused by pedestrian density and pedestrian occlusion under a fixed viewing angle.…”
Section: One-stage Detection Methodsmentioning
confidence: 99%
“…In terms of performance levels, this method surpasses existing approaches such as histogram of oriented gradients [41], scale-invariant feature transform [42], speeded-up robust features [43], oriented fast and rotated binary robust independent element features [44], and binary robust invariant scalable key points [45]. Wearing safety helmets was also considered as the focus of detection for construction personnel [1,2]. The study trained the safety-helmet detection model through a Faster R-CNN and expanded the original dataset through the construction of a new dataset, enriching the applicability of the detector in various environments.…”
Section: Two-stage Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors try to make the CV more trustable in the real world by doing an alarm system by integrating it and also a reporting system with a certain time period. Wang et al (2021a) used human identity recognition and helmet detection using YOLOv3 in a construction site. Nath, Behzadan & Paal (2020) presented a PPE detector using YOLOv3 algorithm.…”
Section: Related Workmentioning
confidence: 99%